Political Communication Model in Egy Sunardi Nurdin's Winning in the Village Head Election - Andi Astinah Adnan; Muhammad Rais Rahmat Razak; Adam Latif; Muh. Rusdi; Hariyanto Hariyanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The High community participation in participating in village head elections indicates intense competition between candidates, so a strategy is needed to build communication with the community, especially by holding village head elections simultaneously and including candidates with a background of former contextual candidates. The purpose of this research is to find out the political communication model in winning Egy Sunardi Nurdin in the 2021 election for the Head of Compong Village, Pitu Riase District, Sidenreng Rappang Regency. The research method used is a descriptive qualitative method. By using purposive sampling technique. Observations, interviews. Research documents were collected and processed using the Nvivo 12 Plus data analysis technique. The results of the study show that the political communication model used by Egy Sunardi Nurdin when communicating with the public uses political communication as measured by indicators; political communicators, political messages, channels or media, goals or targets and influence or effects of political communication. All indicators have been implemented properly. In contrast to the previous context, the most dominant indicator used in the 2021 village head election is "political messages" which are conveyed by means of an approach through various activities such as being present at any time when there is grief for residents, celebrating residents, being active in building friendship and being actively involved in solving problems that arise. faced by residents and actively involved in the activities of the younger generation. This strategy has proven to be effectively used by Egy Sunardi Nurdin in winning the context of direct Village Head elections in 2021 in Compong Village.